Sistem Informasi Inventory dengan Metode Economy Order Quantity dan Reorder Point pada Persediaan Barang Dagang - Febria Sylvana; Hari Marfalino (Jurnal Informatika Ekonomi Bisnis, 2020)
CV. Muaro Radio is a trading company that meets the needs of the community for the needs of electronic goods. All traded goods are imported from distributors in the form of not built up. So it takes time to assemble (production) before being marketed. This process will hamper sales if the goods are not available. So, this research helps companies in maintaining the stability of the availability of goods in order to increase sales. The method used is Economy Order Quantity and Reorder Points. The data that is processed is inventory data and the sale of goods every day. The results of this study can maintain the supply of goods very well in managing stock of goods. So this research is very helpful for CV. Muaro Radio in increasing the company's revenue.